2022
DOI: 10.3390/nu14132747
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and Immunity in Perinatal Hypoxic-Ischemic Injury

Abstract: Perinatal hypoxia ischaemia (PHI), acute and chronic, may be associated with considerable adverse outcomes in the foetus and neonate. The molecular and cellular mechanisms of injury and repair associated with PHI in the perinate are not completely understood. Increasing evidence is mounting for the role of nutrients and bioactive food components in immune development, function and repair in PHI. In this review, we explore current concepts around the neonatal immune response to PHI with a specific emphasis on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Our study showed a specific increase in the risk of mortality due to respiratory diseases between the 50th and 150th days of life. This might have been possible due to a cumulative effect of critical negative factors during early infancy, for example, immunological immaturity and deteriorated response to infections, poor defense mechanisms, incomplete vaccination schedule, or transient iron deficiency [40][41][42][43]. There is also a possibility that some additive physiological or pathogenic mechanisms are involved in exacerbating the health issues, including an increased risk of morbidity and mortality between the second and the fourth month of age.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed a specific increase in the risk of mortality due to respiratory diseases between the 50th and 150th days of life. This might have been possible due to a cumulative effect of critical negative factors during early infancy, for example, immunological immaturity and deteriorated response to infections, poor defense mechanisms, incomplete vaccination schedule, or transient iron deficiency [40][41][42][43]. There is also a possibility that some additive physiological or pathogenic mechanisms are involved in exacerbating the health issues, including an increased risk of morbidity and mortality between the second and the fourth month of age.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular‐molecular mechanisms of the role of metabolic diseases in the damage caused by HI in the newborn are not well understood. However, there is increasing evidence on the role of nutrition and metabolic diseases in the immune response and repair in neonatal HI (Gandecha et al, 2022; Maiuolo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that suffering from metabolic diseases increases the level of inflammation in the brain tissue (Gandecha et al, 2022; Maiuolo et al, 2021; Sadeghi et al, 2016). Also, the increase in inflammation following metabolic diseases leads to an increase in the expression of genes related to the apoptosis of nerve cells, such as Bcl‐2 and caspase‐3 (Gandecha et al, 2022; Maiuolo et al, 2021; Sadeghi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%